Economic Feasibility of Projects Managerial and Engineering Practice - Tang, S. L. (Siu-lam) (Book collections on Project MUSE., 2003)
"This is a textbook for engineering and management/business undergraduates and postgraduate students and reference for practicing engineers or managers who are familiar with their projects but less familiar with financial/economic analysis methods. In this new edition, the chapters have been revised and expanded with the latest theories and data added, especially the most up-dated information on the development of the theories of internal rate of return and net present worth."--Jacket.